ДО ПИТАННЯ ЕТНОПОЛІТИКИ ЦАРСЬКОЇ РОСІЇ (Zaporizhzhia Historical Review, 2021)
Having been tempted by considerable privileges of Catherine II Manifest, Germans moved to Russia, particularly to its southern region. Energy, power, diligence, intellect, knowledge and conscientiousness of some generations of German immigrants mode them rich. Hover, Russian chauvinists were concerned by the fast that foreigners owned many fertile lands. An the 70 certain privileges were canceled, and laws on German opyoke liquidation (1915) led to land and property confiscation and to deportation of Germans.